2020
DOI: 10.5672/apunts.2014-0983.es.(2020/1).139.09
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between School Violence, Sportspersonship and Personal and Social Responsibility in Students

Abstract: Relación entre violencia escolar, deportividad y responsabilidad personal y social en estudiantes PEDAGOGÍA DEPORTIVA

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 7 publications
(9 reference statements)
0
10
0
Order By: Relevance
“…Thus, the TPSR is positioned as an appropriate pedagogical model to promote education in values, reduce school violence [ 3 , 70 , 71 ], and promote student autonomy [ 70 ], since new teaching approaches focused on student interests allow for greater satisfaction of BPN and greater intrinsic motivation values, resulting in better social behavior among students. In the present study, it is observed how both variables positively and significantly predicted students’ prosocial behavior.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, the TPSR is positioned as an appropriate pedagogical model to promote education in values, reduce school violence [ 3 , 70 , 71 ], and promote student autonomy [ 70 ], since new teaching approaches focused on student interests allow for greater satisfaction of BPN and greater intrinsic motivation values, resulting in better social behavior among students. In the present study, it is observed how both variables positively and significantly predicted students’ prosocial behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-adolescence and adolescence are considered to be stages of life in which externalizing problems, such as antisocial behavior (understood as behavior that intentionally causes harm or damage to another person [ 1 ]) or violence, and internalizing problems, such as shyness or social anxiety [ 2 ], increase significantly, with violence being considered one of the most important factors that the education system must address at the international level [ 3 ]. This is due to its close relationship with antisocial behavior and its association with negative consequences on mental health and personal, social, and school adjustment [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…2. On the other hand, the influence of responsibility on the activity and behavior of students has been proven, for example, violence in school decreases with high responsibility [9]. The question arises: what is the relation between the involvement in various types of socially significant activities and responsibility?…”
Section: Introductionmentioning
confidence: 99%